„Market” activities of the Protestant minority community with regard to the use of digitalization based on the Pentecostal DOM Church - Apanasewicz-Burcon, Jagoda (Człowiek i Społeczeństwo, 2025)
The article concerns the studied Protestant minority community – the DOM Church in Warsaw – and the marketing strategy it uses to strengthen the position of this group in the Polish religious market. The elements of digitization and the use of new media were discussed, as part of evangelization activities, which might attract the interested persons from all age groups. The analysed material was obtained from the international research project entitled „RECOVIRA. Digitization and European religious communities. Response to the pandemic.” Ethnography, including in-depth interviews, participant observation and netography were used within the project. Based on the analysis of interviews with: the pastor of the Church, community members, and the team for social media, the main aspects of the marketing strategy of the studied religious community were presented.